FAKTOR-FAKTOR YANG MEMENGARUHI EFEKTIVITAS KERJA PERAWAT PADA RUMAH SAKIT MITRA SEJATI MEDAN - Sitompul, Pandapotan; Tinambunan, Anitha Paulina; Silalahi, Donalson; Hutapea, Putri Wildasari br. (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aimed to identify and explain the factors influencing work performance at Mitra Sejati Hospital in Medan. Data were obtained directly from respondents (nurses) at Mitra Sejati Hospital, Medan. The total number of people in this study is 82 employees and the sample size was taken using the saturated sampling technique, so the research sample is 5x14 = 70 people. The analytical techniques used in this study were validity and reliability testing and factor analysis testing. The results of this study show that the factors affecting work performance at Mitra Sejati Medan Hospital are organizational characteristics, environmental characteristics, employee characteristics, management policies and practices, and responsibilities. service, productivity, motivation, job evaluation, supervision, equipment, facilities, quantity. quality, work discipline and remuneration. The KMO figure of the Measure of Sampling Adequacy (MSA) is 0.765 out of 0.50, which has a significance of 0.000, thus this variable is suitable for further analysis using factor analysis. Judging from the value of the correlation coefficient, the most dominant factor affecting work efficiency at Mitra Sejati Medan Hospital is the task factor (0.836).